FEASIBILITY STUDY AND FLOOR ADDITIONAL PLAN WITH CONCRETE JACKETING STRENGTHENING METHOD - I Putu Nida Verdi Antara; I Nengah Sinarta; Ni Made Widya Pratiwi; I Putu Ellsa Sarassantika; I Gede Dhana Putra Sanjaya (Master Program of Infrastructure and Environmental Engineering, Postgraduate Program, Warmadewa University, 2024)
Concrete Jacketing is a method of strengthening reinforced concrete structures that is applied to buildings to increase and improve their strength capacity. Concrete Jacketing is carried out by enlarging the existing reinforced concrete cross section with an additional layer of concrete which is also reinforced with reinforcement. The structure of the Taruna Warmadewa Vocational School building is planned to be given additional floors, from 2 floors to 3 floors. Prior to adding the floor, a feasibility study was carried out for testing the existing material, to determine the quality of the material to be used in the analysis. Based on the results of material testing of the existing structure, the structure of SMK Taruna Warmadewa needs to be strengthened. Therefore, concrete jacketing was chosen as an effective reinforcement method to increase the capacity of the structure to carry loads due to the addition of floors. The method of collecting data in carrying out a feasibility study and planning for additional floors in the Taruna Warmadewa Vocational School is the method of literature study, direct observation, material testing and modeling analysis. The analysis determined that concrete jacketing was required for all columns and two types of beams. Specifically, column dimensions were increased from 30 cm × 50 cm to 50 cm × 70 cm (K1), primary beams from 30 cm × 45 cm to 35 cm × 55 cm (B1), and secondary beams from 20 cm × 30 cm to 30 cm × 45 cm (B2). The pile cap foundation thickness was increased from 30 cm to 70 cm, with plan dimensions of 2 m × 2 m. For the new third floor, the design specifies columns of 45 cm × 45 cm (K1) and three beam types: 30 cm × 50 cm (B1), 25 cm × 40 cm (B2), and 20 cm × 30 cm (B3).